2018
DOI: 10.1016/j.nrjag.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Iron ore prospecting based on very low frequency-electromagnetic and geoelectrical resistivity at Wadi Abu Subeira, Northeastern Aswan, South Egypt

Abstract: The serious need and high demand of iron oxides in cement industry urges to carry out critical investigation in vicinity of cement factories in South Egypt Governorates. The considered area Wadi Abu Subeira lies to the north east of Aswan. The possible occurrences of hematite in the subsurface enforced to carry out some geophysical measurements in the in the form of very low frequency-electromagnetic and geoelectrical resistivity. A total number of 684 very low frequency-electromagnetic and 54 vertical electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
(8 reference statements)
0
15
0
Order By: Relevance
“…It was observed that both criteria act well, giving suitable values of the regularization parameter in the enormous majority of situations (Ghanati et al, 2017;Ghanati et al, 2015). The integrative use of both the Very Low Frequency Electromagnetic (VLF-EM) and geoelectrical resistivity sounding techniques was found effective by Youssef et al in 2018 for imaging the typical shallow stratigraphic sequence at the study area. The obtained data sets were comprehensively and steadily inverted/transformed in subsurface electric resistivity/EM-equivalent current-density.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…It was observed that both criteria act well, giving suitable values of the regularization parameter in the enormous majority of situations (Ghanati et al, 2017;Ghanati et al, 2015). The integrative use of both the Very Low Frequency Electromagnetic (VLF-EM) and geoelectrical resistivity sounding techniques was found effective by Youssef et al in 2018 for imaging the typical shallow stratigraphic sequence at the study area. The obtained data sets were comprehensively and steadily inverted/transformed in subsurface electric resistivity/EM-equivalent current-density.…”
Section: Introductionmentioning
confidence: 93%
“…Gangue minerals mainly consist of actinolite, epidote, tourmaline, biotite, calcite, quartz, and minor titanite and apatite distributed as veins and veinlets, and they vary in thickness a few millimeters to a few centimeters along cracks of magnetite. Magnetite is the most dominant iron mineral in the deposit; although, due to the effects of oxidation and supergene processes, locally magnetite has been martitized along grain boundaries and fractures (Rostami Paydar et al, 2009;Youssef et al, 2018).…”
Section: Geological Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average values of resistivity of geological formations can be deduced by conducting several standard soundings [22]. We present below some calibration soundings.…”
Section: Calibration Of Electrical Soundingsmentioning
confidence: 99%
“…Geoelectrical methods are very commonly used in conducting subsoil or subsurface investigations for various cases. Many studies have been done on this subject as follows: geotechnical and engineering site investigations (Nur Islami, 2019); groundwater explorations (Island and Balaji, 2013) (Hafeez, Sabet and Zayed, 2018) (Rabeh et al, 2018) (Bayewu et al, 2018) (Aboh, 2015); mapping subsurface structures (Wo and Bania, 2019); mapping of soil and groundwater contamination (Xu et al, 2019) (Ganiyu et al, 2020); environmental studies (Wilson, Ingham and Mcconchie, 2006) (Kumar, Priju and Prasad, 2015) (Fadili et al, 2017); mapping of growth fault (Khalili and Mirzakurdeh, 2019); soil characterization for engineering purposes (Arjwech et al, 2020) (An et al, 2020) (Abudeif et al, 2019); ore deposit explorations (Arjwech et al, 2020) (Youssef, El-gawad and Farag, 2018) (Hariri et al, 2019); archaeological investigations (Yilmaz et al, 2019); bedrock detections (Woźniak and Bania, 2019).…”
Section: Introductionmentioning
confidence: 99%